GEJALA INFERIORITAS PADA SUAMI YANG MEMILIKI ISTRI BERPENGHASILAN LEBIH TINGGI DI KELURAHAN SIDOMULYO BARAT, KECAMATAN TAMPAN, KOTA PEKANBARU - Endila Famelsi; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Social change and modernization today have entered into the basic and smallest institutions within the community, namely the family. The inclusion of these two factors makes the need in the family more and more, it demands for active wife and come to fight for the fulfillment of needs in his family. Most wives have more skills than husbands, so the wife has a great opportunity to work and earn on the husband. This phenomenon will cause inferioritas or keminderan symptoms in the husband. This study uses qualitative methods, namely data collection obtained based on the reality of field data through observation, interviews, and documentation. The research informant consisted of 4 pairs of husband and wife, but the subject of research only focused on husband. To strengthen the writing, researchers collect data from reports and documents, books, online media and publications. The theoretical framework used in this research is the theory of social change and gender relations. The results showed that of the four infromants that researchers carefully, then obtained the results that there are symptoms of inferiority in the husband who has a wife of higher income. This inferiority not only affects the husband, but also affects the social environment.Keywords: Symptoms of Inferiority, Income, Husband